Peran Manajerial Kepala Sekolah Dalam Pengelolaan Kegiatan Ekstrakurikuler Pramuka - Febrianty, Dwi; Annur, Saipul; Safitri, Dian (El-Idare, 2025)
This study aims to analyze the role of the principal in managing the extracurricular Scouting activities at SMP Sandika Sukajadi, Banyuasin Regency. The research employs a qualitative method with a descriptive approach, allowing for an in-depth understanding of the studied phenomenon. Data collection techniques include observation, interviews, and documentation, with key informants consisting of the principal, Scout advisors, and the extracurricular unit leader. The findings indicate that the principal plays a strategic role in managing Scouting activities through three main aspects: planning, organizing, and implementation. In the planning stage, the principal collaborates with Scout advisors to design activity programs that support students’ character development while ensuring adequate resource allocation. In organizing, the principal is responsible for determining the organizational structure, appointing competent advisors, and managing the necessary facilities and infrastructure. In implementation, the principal mobilizes human resources and provides support to ensure the sustainability of Scouting activities, including leadership training and student participation in various programs. Challenges faced include budget constraints, lack of active student involvement, and limitations in facility availability. To address these issues, the principal optimizes school operational funds (BOS), establishes collaborations with external parties, and organizes training for advisors. Through effective leadership, Scouting activities at SMP Sandika Sukajadi can be optimally conducted to foster students' character and skills.